Biological effects of atmospheric particulate matter: cytotoxicity and metabolic alterations in pulmonary and neuronal cells - Silva, Tatiana Deolinda dos Santos Teixeira da (2024)
Growing concerns about the health impacts of atmospheric particulate matter (PM), identified as a risk factor for pulmonary, cardiac and neurological diseases, highlight the pressing need for a thorough examination of the cellular and molecular events responsible for PM-induced damage. This thesis aims to provide new insights into the biological effects of PM of different sources and sizes, particularly PM₁₀ and PM₂.₅, with diameters below 10 and 2.5 μm, respectively. The studies reported employed cell models of both lung and neuronal origin, chosen due to the significance of the respiratory and nervous systems as primary targets of PM exposure. Furthermore, integration of cellular metabolic profiling (metabolomics) with conventional toxicity assessments aimed to enhance our comprehension of PM's biological impacts. In Chapter II, we investigated the response of human alveolar epithelial cells (A549) to organic extracts of PM10 collected from different locations within a Portuguese city. Our findings revealed diminished cell viability, increased generation of reactive oxygen species (ROS), changes in mitochondrial membrane potential, cell cycle arrest at G0/G1 phase, and modulation of intracellular metabolism. The extract richer in polycyclic aromatic hydrocarbons and plasticizers had a more pronounced metabolic impact, suggesting stimulation of glycolysis and the build-up of antioxidant defenses (glutathione), possibly to counteract mitochondrial dysfunction. In Chapter III, we aimed to compare the effects of PM₂.₅ (originating from São Paulo, Brazil) on 2D and 3D models of human bronchial epithelial cells (16HBE). The consistency of results between monolayered cells and spheroids largely depended on the biological endpoints being examined. While 2D-cultured cells exhibited more pronounced impacts on cell viability, oxidative stress, and metabolic behavior, alterations in pro-inflammatory cytokines were more noticeable in spheroids. On the other hand, the results of the apoptosis/necrosis assay were similar between the two culture formats. Overall, these findings emphasize the importance of contemplating different cell culture models when evaluating the effects of environmental exposures on respiratory epithelial cells. Finally, in Chapter IV, the cytotoxic and metabolic effects of PM2.5 organic extracts on human neuronal cells (SH-SY5Y) were investigated. A dose- and time-dependent decrease in cell viability was observed, with various biological effects apparent even at concentrations resulting in minor viability declines (≤ 30%). These effects included the induction of early apoptosis, the production of ROS and tumor necrosis factor-alpha (TNF-α), as well as notable alterations in cell metabolism. Specifically, metabolomics results suggested a downregulation of glycolysis and mitochondrial respiration, coupled with the activation of alternative energy-producing pathways such as proline oxidation and the creatine-phosphocreatine system. Furthermore, there appeared to be a downregulation in one-carbon metabolism, alongside the accumulation of neutral lipids and glutathione. Altogether, by integrating conventional toxicological assessments and metabolomics in relevant cell models, this work contributed to improved understanding of PM toxicity, underscoring the importance of multifaceted experimental approaches for evaluating environmental health risks.